Analysis of MSME Capital Using Sharia Fintech Peer to Peer Lending: Analisa Permodalan UMKM Menggunakan Fintech Peer to Peer Lending Syariah - Latifah, Fitri Nur; Adriani , Ninda; Ariyanti, Novia; Batubara, Sultan Saladin (Universitas Muhammadiyah Sidoarjo, 2023)
As one of the pillars of the economy in Indonesia, it is proven that MSMEs are able to survive the Covid-19 pandemic with various innovations they have implemented, but there are still several obstacles in the development of MSMEs themselves. MSMEs, especially for the micro business scale in Indonesia, are still classified into segments that have limited access to formal financial institutions (unbankable population). The results of the PWC survey in 2019 The biggest problem of MSMEs is the problem of capital, and in an effort to obtain additional capital, around 74% of the micro segment cannot access financing from the formal financial sector. Increasing access to finance itself is one of the strategies to achieve Sustainable Development Goals (SDGs). Based on previous research, Islamic fintech has a role in driving SDGs targets, especially the targets to (1) eradicate poverty and (2) hunger, and (3) reduce inequality in wealth distribution. In this study we conducted indepth interviews with several MSME players and Islamic fintech companies. The lack of literacy related to fintech with the sharia peer to peer lending scheme makes MSMEs afraid to do business financing with this scheme, even though this scheme is very suitable for the unbankable population because the financing requirements are easy and fast in the disbursement process.